Mixing of superconducting d(x2-y2) state with s-wave states for different filling and temperature - Ghosh, A.; Adhikari, S. K. (Elsevier B.V., 2001)
We study the order parameter for mixed-symmetry states involving a major d(x2-y2) state and various minor s-wave states (s, s(xy), and Sx2+y2) for different filling and temperature for mixing angles 0 and pi /2. We employ a two-dimensional tight-binding model incorporating second-neighbor hopping for tetragonal and orthorhombic lattice. There is mixing for the symmetric s state both on tetragonal and orthorhombic lattice. The s(xy) state mixes with the d(x2-y2) state only on orthorhombic lattice. The s(x2+y2) state never mixes with the d(x2-y2) state. The temperature dependence of the order parameters is also studied. (C) 2001 Elsevier B.V. B.V. All rights reserved.
Keywords: high-T-c superconductor; mixed-symmetry state; order parameter